Tinjauan Ekonomi Islam Terhadap Manajemen Keuangan Pada Industri Rumahan Jilbab Muizz Collection - Farhana, Nora Farita; Anwar, Moch. Khoirul (Universitas Negeri Surabaya, 2018)
Islam has always urged adherents working and improving the work ethic. It encourages its adherents to Islam to plunge into entrepreneurs (entrepreneurs). One of the types of businesses that are thriving in Indonesia is small and medium scale business (UMKM). One of the Small Medium Enterprises that started developing right now is